Innovative strategies and frameworks in climate change adaptation emerging research and opportunities - Flor, Alexander G., 1953- (IGI Global, 2018)
"This book is about climate change adaptation within the most basic of sectors - food and agriculture. It discusses research strategies and frameworks on climate change adaptation. Although these strategies and frameworks were based on the Philippines' experience, it is applicable to most countries in the Global South, specifically the most vulnerable to conditions associated with changing climates"--